THE EVOLUTION OF STUDENTS MILITANCY IN A GLOBALIZING WORLD: TRENDS AND PATTERNS IN KENYA - Ngesu, Lewis Muli (IJRDO- Journal of Educational Research, 2017)
Student militancy as a widespread phenomenon in Africa, mainly since the 1960’s, is the subject of a much older and wider “youth phenomenon” dating as far back as the middle ages, and spread widely across Europe in countries such as France, Italy, Germany and England, where the movement initially confined itself to the university campuses and centred on disobedience to authority (for example, the king and his delegates) and on the refusal to be disciplined (Hobber in Lipest and Altbach, 1969: v, Ngesu 2013). Since the mid-1960’s and more intensively in the 1970’s nearly every Africa country had in one way or another experienced a shake up by students outbreaks (Ishumi, 1976). Such countries include Egypt, Senegal, Nigeria, Ghana, Cameroon, South Africa and Ethiopia. Again the triggering causes varied and were frequently shaped by local situations but closer examination reveals a basic struggle for “power’ to influence and/or actually participate in the affairs of national politics and education ranging from formulation of national goals and policies to formulation of school/college curricula to internal and external administration of the educational and cultural institutions (Ishumi, 1976, Ngesu et al 2013). Closer home the first case of student indiscipline was reported in Maseno in1908 when students refused to participate in manual labour and pressed for more reading and writing (Anderson 1970, 135). Three years later Mumias School went on strike against colonial administration (Ngesu et al 2013).